Human Rights From Below : Achieving rights through community development - Ife, Jim (Cambridge University Press, 2010)
In Human Rights from Below, Jim Ife shows how human rights and community development are problematic terms but powerful ideals, and that each is essential for understanding and practising the other. Ife contests that practitioners – advocates, activists, workers and volunteers – can better empower and protect communities when human rights are treated as more than just a specialist branch of law or international relations, and that human rights can be better realised when community development principles are applied. The book offers a long overdue assessment of how human rights and community development are invariably interconnected. It highlights how critical it is to understand the two as a basis for thinking about and taking action to address the serious challenges facing the world in the twenty-first century. Written both for students and for community development and human rights workers, Human Rights from Below brings together the important fields of human rights and community development, to enrich our thinking of both.